Results of tax transparency standards implementation in the Organization of economic cooperation and development - N. A. Poponova (Путеводитель предпринимателя, 2020)
The study subject is the measures of suppression so called «Harmful tax competition» process and the world financial system transparency increasing, as well as international taxation rules transparency increasing. These measures are taken by Organization of economic cooperation and development (OECD) and European Union (EU) countries since the mid of 2000. This study describes their main results. The theme of Russian Federation participation in the process of international automatic tax information exchange is touched.Conclusions were drawn about the increase of the level of tax legislation so as to reach the international level in field of compliance. It has done due to implementation of the financial information automatic exchange standard.Also the aspect of inefficiency of the most traditional schemes of international tax optimization in the future are touched. The negative aspects of the international exchange of tax information were also noted.